Análisis exergético y de segunda ley del esquema tecnológico para la producción de etanol anhidro por destilación extractiva (2018)
The research group of unconventional separation processes (GPS) of the Fundación Universidad de América has previously carried out research into the production of anhydrous ethanol, as well as the energy expenditure that occurs in its production. Being this an alternative for the reduction of the consumption of fossil fuels since it is produced from renewable sources and generates an oxygenated combustion with less emission of toxic gases to the environment. In this project the continuation of the research project is presented. Energy evaluation of technological schemes for the production of anhydrous ethanol by extractive distillation to which an exergytic and second-law analysis of thermodynamics is incorporated. Initially, the incorporation of material, energy, entropy and exergy balances is presented to the technological scheme which is carried out in the Aspen HYSYS v9.0 process simulator. Subsequently, the work lost is calculated by entropy generated and exergy destroyed, resulting in 370.71 kJ / s and 370.59 kJ / s respectively, as well as the second law efficiencies of thermodynamics for each of the present equipment as they are; the extractive column (33.62%), recovery column (13.09%), heat exchanger (69.47%), mixer (100%) and pump (19.28%), carrying out each of mathematical operations in the tool provided by the simulator called Spreadsheet. Additionally, the inclusion of the parameter sensitivity study carried out in Aspen HYSYS v9.0 and Aspen Plus v9.0 is presented to reduce the energy expenditure of the process and ending with the implementation of the modifications to the operating variables that generate a reduction in the loss of work, making it decrease to 214,770 kJ / s. From the above, the importance of the implementation of the second law analysis is observed since it can be considered the reduction of energy losses as for the present project in 42.01%